Fishing for the Big Boys: Competing Interests Under the Fisheries Act 1996 - Boyd, Jordan (Victoria University of Wellington Law Review, 2010)
This article examines the effect of two recent and connected developments on fisheries management in New Zealand. The first development is a change to s 13 of the Fisheries Act 1996, that Act’s central operative sustainability provision. The second development is the Supreme Court’s decision in the Kahawai case. This article argues that these two developments mean that the operation and interpretation of the Fisheries Act favour commercial interests over recreational ones. It argues that the minority’s interpretation in the Kahawai case was correct and that, therefore, the change to s 13 was unnecessary. This article concludes that the structural bias in the Fisheries Act is undesirable, as catch allowance decisions are (and should be) essentially political.